2000
DOI: 10.1136/heart.84.5.522
|View full text |Cite
|
Sign up to set email alerts
|

Is provisional stenting the effective option? The WIDEST study (Wiktor stent in de novo stenosis)

Abstract: Aim-To compare the immediate and late outcomes of patients treated by a policy of routine stent implantation with routine balloon angioplasty and the use of stents only when an ideal result has not been obtained. Methods-A nine centre, multinational, randomised study of 300 patients with coronary artery disease thought suitable for treatment of a single lesion by balloon angioplasty or stent implantation. Only new lesions in patients who had not undergone previous bypass surgery were included, and totally occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…10,11,13,19 Our immediate and late results were consistent with reports of IVUS-guided PTCA, with a similar rate of crossover to stent. [17][18][19] …”
Section: Immediate Resultssupporting
confidence: 80%
“…10,11,13,19 Our immediate and late results were consistent with reports of IVUS-guided PTCA, with a similar rate of crossover to stent. [17][18][19] …”
Section: Immediate Resultssupporting
confidence: 80%
“…In 29 studies, clinical follow-up was available at 6 months; however, few studies reported on the longer term outcomes for each intervention arm. Thirteen studies 38,39,42,43,49,53,54,56,57,63,65,69,77 reported outcomes at 1 year, two studies 61,67 at 2 years, one study 52 at 4 years and in one study the longest period of follow-up was 5 years. 38 Three studies 45,68,86 reported on follow-up separately for those with diabetes mellitus (DM).…”
Section: Follow-upmentioning
confidence: 99%
“…However, the comparison of DES and BMS for single-vessel disease does not involve any question of mortality and therefore can easily be represented in a much simpler way. [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]70+ CIC In this section we introduce a simplified model for this purpose, which can be presented on a single Excel worksheet and encapsulates virtually all the detail of the original LRIG model for comparison of stents.…”
Section: Economic Modelling: Simplified Model For Non-drug Eluting Vementioning
confidence: 99%
See 2 more Smart Citations